Increased rates of large‐magnitude explosive eruptions in Japan in the late Neogene and Quaternary. (1st July 2016) - Mahony, S. H.; Sparks, R. S. J.; Wallace, L. M.; Engwell, S. L.; Scourse, E. M.; Barnard, N. H.; Kandlbauer, J.; Brown, S. K.
Abstract: Tephra layers in marine sediment cores from scientific ocean drilling largely record high‐magnitude silicic explosive eruptions in the Japan arc for up to the last 20 million years. Analysis of the thickness variation with distance of 180 tephra layers from a global data set suggests that the majority of the visible tephra layers used in this study are the products of caldera‐forming eruptions with magnitude (M) > 6, considering their distances at the respective drilling sites to their likely volcanic sources. Frequency of visible tephra layers in cores indicates a marked increase in rates of large magnitude explosive eruptions at ∼8 Ma, 6–4 Ma, and further increase after ∼2 Ma. These changes are attributed to major changes in tectonic plate interactions. Lower rates of large magnitude explosive volcanism in the Miocene are related to a strike‐slip‐dominated boundary (and temporary cessation or deceleration of subduction) between the Philippine Sea Plate and southwest Japan, combined with the possibility that much of the arc in northern Japan was submerged beneath sea level partly due to previous tectonic extension of northern Honshu related to formation of the Sea of Japan. Changes in plate motions and subduction dynamics during the ∼8 Ma to present period led to (1) increased arc‐normal subduction in southwest Japan (and resumption of arc volcanism) and (2) shift from extension to compression of the upper plate in northeast Japan, leading to uplift, crustal thickening and favorable conditions for accumulation of the large volumes of silicic magma needed for explosive caldera‐forming eruptions. Key Points: Increase in volcanic activity in Japan at ∼8, 4–6, and ∼2 Ma Tephra layers in distal sediment cores represent magnitude 6 or greater eruptions Tectonic changes driving rates of explosive volcanism in Japan